Knowledge, Attitude, and Practice towards Medication Errors and Adverse Drug Reaction Reporting among Medicine Students - Maryam Aghakouchakzadeh; Mandana Izadpanah; Ali Yadegari (Research Center for Rational Use of Drugs (RCRUD), 2017)
Background: The most common types of medical error are medication errors (MEs) which defined as any preventable event that may be caused by an inappropriate medication usage and lead to an adverse drug reaction (ADR) event in patients. In recent years, different approaches have been proposed to reduce MEs, one of which is reporting ADRs. The present study was designed to assess the Knowledge, Attitude and Practice (KAP) of medicine students towards MEs and ADRs reporting. Method: The validated 12-item questionnaire included subsequently 4 questions, 5 items and the final 3 questions related to the knowledge, attitude, and practice that was given to each participant before and after of the clerkship course. The study population were 40 students of fourth-year of medicine. Results: Demographic features of the participants have no significant difference. Medicine students had a poor KAP towards MEs. Only 8% of respondents had general knowledge about MEs and 50% of students believed MEs are inevitable events, less than 20% of them were acquainted with 5 rules of prescriptions. Students had good knowledge and attitude but poor practice towards ADRs reporting. 55% of participants were aware of their responsibility of ADRs reporting but only 5% of respondents were acquainted with ADRs reporting method and the ADR center in the hospitals. Conclusion: The educational intervention, alteration in medicine student's curriculum, and hold the interactive clerkship for health care professionals can improve the KAP towards ADRs reporting and diminish of the preventable medication errors.